"We give water or porridge, but we don't really know what the child wants:" a qualitative study on women's perceptions and practises regarding exclusive breastfeeding in Kilimanjaro region, Tanzania - Melina Mgongo; Tamara H. Hussein; Babill Stray-Pedersen; Siri Vangen; Sia E. Msuya; Margareta Wandel (BMC, 2018)
Abstract Background World Health Organization (WHO) recommends exclusive breastfeeding (EBF) as the optimal way to feed infants below 6 months of age. The benefits of EBF are well documented. However, in Tanzania, EBF is still rarely practised. This study explored the knowledge, attitudes and practises of EBF among mothers in Kilimanjaro region of northern Tanzania. Methods This is a qualitative research study. The three districts in Kilimanjaro region namely Same, Moshi Municipal Council and Rombo districts were selected. In each district, three focus group discussions (FGDs) with mothers of infants aged 0-12 months were conducted. A total of 78 mothers participated in the focus group discussion. Results The main result is that most of the mothers had a theoretical knowledge of the benefits of EBF but were not able to practise this knowledge for a range of reasons. The reasons for not practising EBF in real life included poor maternal nutrition, the pressure for women to return to work, inadequate knowledge about expressing breast milk, and perceived insufficiency of milk supply. Additionally, mothers received conflicting advice from a range of sources including close relatives, community members and health care providers, and they often choose the advice of their elders. Mothers also offered suggestions on ways to improve EBF including educating the community on the benefits of EBF. Conclusion The results show that the women need support from close relatives and employers to successfully practise EBF. This presents a need for involving close relatives in EBF interventions, as they are important sources of breastfeeding information in the community. Additionally, behavioural interventions that promote optimal breastfeeding practises might help to improve exclusive breastfeeding.